2019
DOI: 10.1111/jhn.12699
|View full text |Cite|
|
Sign up to set email alerts
|

Concurrent and predictive validity of the Mini Nutritional Assessment Short‐Form and the Geriatric Nutritional Risk Index in older stroke rehabilitation patients

Abstract: BackgroundMalnutrition may worsen clinical outcomes in stroke patients. Few malnutrition screening tools have been validated in the rehabilitation setting. The present study aimed to assess the concurrent and predictive validity of two malnutrition screening tools.MethodsWe retrospectively collected scores for the Mini Nutritional Assessment Short‐Form (MNA‐SF) and the Geriatric Nutritional Risk Index (GNRI) in consecutive stroke patients aged ≥65 years in a rehabilitation hospital. Concurrent validity was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(82 citation statements)
references
References 41 publications
3
78
1
Order By: Relevance
“…However, the probability of a false-positive case may increase if the cutoff values are applied for patients in the rehabilitation setting [23]. Therefore, modified cutoff values for stroke patients undergoing rehabilitation were used: 0-5 (malnourished), 6-7 (at risk of malnutrition), and 8-14 (well-nourished) in addition to the original ones because it showed sufficient validity [24]. Certification for public long-term care insurance was classified into five categories based on national public policy, from "Care level 1," can perform almost all ADL, but required partial care, to "Care level 5," must be aided in all situations and had difficulty with communication.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, the probability of a false-positive case may increase if the cutoff values are applied for patients in the rehabilitation setting [23]. Therefore, modified cutoff values for stroke patients undergoing rehabilitation were used: 0-5 (malnourished), 6-7 (at risk of malnutrition), and 8-14 (well-nourished) in addition to the original ones because it showed sufficient validity [24]. Certification for public long-term care insurance was classified into five categories based on national public policy, from "Care level 1," can perform almost all ADL, but required partial care, to "Care level 5," must be aided in all situations and had difficulty with communication.…”
Section: Data Collectionmentioning
confidence: 99%
“…Thus, as optimal nutritional intervention may improve cognitive performance in malnutritional stroke patients, it is crucial to assess the premorbid nutritional status following an ischemic stroke. Recently, several different screening tools have been used for the assessment of the nutritional status in stroke patients including the Mini Nutritional Assessment Short-Form (MNA-SF) and the Malnutrition Universal Screening Tool (MUST) [ 11 , 12 , 13 ]. However, it is not easy for stroke patients and caregivers to complete a structured questionnaire or describe accurately whether they experienced psychological stress or weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…The GNRI has already been validated for the prediction of outcomes after a cardiovascular disease, and a recent study has revealed its prognostic value as regards short-term functional outcomes after a stroke [ 7 ]. It has also been validated via correlation with traditional nutritional indices, including the MNA-SF and the MUST in stroke patients [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Up to 10.5% of community-dwelling seniors, 7.7% of nursing home residents and 14% of hospitalised patients experience unintentional weight loss [ 1 ]. Disabled older adults admitted to rehabilitation hospitals, units or wards are particularly susceptible to worsened nutritional status with a prevalence of 13–30%, and reports suggest a remarkably high proportion (92%) of poor nutritional status in tube-fed patients [ 2 , 3 , 4 , 5 ]. Malnutrition may result in muscle attenuation, which can result in a decline in functional capacity in older patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%